While performing multiplication of three or more numbers, the product remains the same even if we change the order of grouping the numbers.

**(a x b) x c = a x (b x c)**

In order to verify this property, let us consider three integers and apply the associative property of multiplication.

Consider the following :

** a ** | ** b ** | ** c ** | ** (a x b) x c ** | ** a x (b x c) ** |

2 | 5 | 7 | (2 x 5) x 7 = 10 x 7 = 70 | 2 x (5 x 7) = 2 x 35 = 70 |

Here, 2, 5 and 7 are integers. In this case, (2 x 5) x 7 = 2 x (5 x 7) = 70.

** a ** | ** b ** | ** c ** | ** (a x b) x c ** | ** a x (b x c) ** |

2 | 0 | -7 | (2 x 0) x (-7) = 0 x (-7) = 0 | 2 x [0 x (-7)] = 2 x 0 = 0 |

Here, 2, 0 and -7 are integers. In this case, (2 x 0) x (-7) = 2 x [0 x (-7)] = 0.

** a ** | ** b ** | ** c ** | ** (a x b) x c ** | ** a x (b x c) ** |

-9 | 3 | -4 | [(-9) x 3] x (-4) = (-27) x (- 4) = 108 | -9 x [3 x (-4)] = (-9) x (-12) = 108 |

Here, -9, 3 and -4 are integers. In this case, [(-9) x 3] x (-4) = -9 x [3 x (-4)] = 108.